2011
DOI: 10.1074/jbc.m111.260711
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Regulating the Trafficking and Turnover of Pannexin1 Protein and the Role of the C-terminal Domain

Abstract: Pannexin1 (Panx1) is an integral membrane protein comprised of three species as follows: an unglycosylated core-Gly0, a high mannose-Gly1, and a complex glycosylated Gly2 species. Although Panx1 channels mediate several cellular responses, the domain regulating its oligomerization and cell surface trafficking and the mechanisms governing its internalization and degradation have not been identified. This study characterizes the role of the Panx1 C-tail domain by truncating the polypeptide at residue 307 and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 40 publications
(62 reference statements)
3
42
0
Order By: Relevance
“…The current study lends further support to a growing body of work indicating that the Panx1 C-terminus is important for traffi cking (Gehi et al, 2011). The localization of chimeric Panx2 with the C-terminus of Panx1 was distinct from wildtype Panx2 expression, suggesting that elements within the Panx2 C-terminus are critical for its proper localization and are absent from the Panx1 C-terminus.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The current study lends further support to a growing body of work indicating that the Panx1 C-terminus is important for traffi cking (Gehi et al, 2011). The localization of chimeric Panx2 with the C-terminus of Panx1 was distinct from wildtype Panx2 expression, suggesting that elements within the Panx2 C-terminus are critical for its proper localization and are absent from the Panx1 C-terminus.…”
Section: Discussionsupporting
confidence: 53%
“…One of the more recently emerging vital structural components in traffi cking of Panx1 is its C-terminus (Gehi et al, 2011). This region is quite dissimilar between Panx1 and Panx2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once Panx1 is destined to internalize, our own studies using inhibitors of lysosomal function 41 as well as other studies that showed colocalization of Panx1 with lysotracker 29 suggest that Panx1 is destined for ultimate lysosomal degradation (Figure 4). However, the pathways involved in classical endocytic internalization, including clathrin, dynamin II, and caveolins-1 and -2, do not appear to be engaged in the internalization of Panx1.…”
Section: Protein Internalization and Degradationmentioning
confidence: 99%
“…However, the pathways involved in classical endocytic internalization, including clathrin, dynamin II, and caveolins-1 and -2, do not appear to be engaged in the internalization of Panx1. 41 Therefore, Panx1 internalization may be governed by molecular machinery that could potentially involve actin microfilaments. 39 …”
Section: Protein Internalization and Degradationmentioning
confidence: 99%